Characterization of Human Mesenchymal Stem Cells Isolated from the Testis. (3rd September 2018) - De Chiara, Letizia; Famulari, Elvira Smeralda; Fagoonee, Sharmila; van Daalen, Saskia K. M.; Buttiglieri, Stefano; Revelli, Alberto; Tolosano, Emanuela; Silengo, Lorenzo; van Pelt, Ans M. M.; Altruda, Fiorella
Abstract : Mesenchymal stem cells hold great promise for regenerative medicine as they can be easily isolated from different sources such as adipose tissue, bone marrow, and umbilical cord blood. Spontaneously arising pluripotent stem cells can be obtained in culture from murine spermatogonial stem cells (SSCs), while the pluripotency of the human counterpart remains a matter of debate. Recent gene expression profiling studies have demonstrated that embryonic stem cell- (ESC-) like cells obtained from the human testis are indeed closer to mesenchymal stem cells (MSCs) than to pluripotent stem cells. Here, we confirm that colonies derived from human testicular cultures, with our isolation protocol, are of mesenchymal origin and do not arise from spermatogonial stem cells (SSCs). The testis, thus, provides an important and accessible source of MSCs (tMSCs) that can be potentially used for nephrotoxicity testing in vitro . We further demonstrate, for the first time, that tMSCs are able to secrete microvesicles that could possibly be applied to the treatment of various chronic diseases, such as those affecting the kidney.